ETNOMATEMATIKA PADA PENANGGALAN JAWA TERKAIT ARITMETIKA DI DESA YOSOMULYO - Agustina, Leni Ofta; Sunardi, Sunardi; Susanto, Susanto (Kadikma, 2016)
Abstract. This research aims to describe the form of the etnomathematics in calculation of Javanese calendar related to arithmetic used in cultural activities and daily activities in the Yosomulyo village. This research’s type is descriptive research with qualitative approach to etnography. Data collection methods which are used in this research are observation and interview. Subject for this research are community leaders as much as two people and communities as much as five people who understand in calculation of Javanese calendar. The results showed that calculation of Javanese calendar count the cultural activities and daily activities associated arithmetic modulo systems, activities that appears are calculation of the day and the pasaran, calculation of the ceremony commemorating the death and the pregnancy, as well as determine the day and the right plants in the farm. Modulo is used modulo 3, 4, 5, and 7. the calculations use modulo 3 is calculation in determining the day of wedding. Calculations using modulo 4 is calculation to determine the day and the right plants in the farm. Calculations using modulo 5 is calculation to determine pasaran an activity. Calculations using modulo 7 is calculation to determine the day an activity. Keywords : Etnomathematics, Javanese Calendar, Modulo.